Electron states at the Si–SiO₂ boundary (Review) - Primachenko, V.E.; Kirillova, S.I.; Venger, E.F.; Chernobai, V.A. (Semiconductor Physics Quantum Electronics & Optoelectronics, 2005)
This review is aimed at analysis of the system of discrete and continuously distributed boundary electron states (BES) on (111) and (100) silicon surfaces in the Si-SiO₂ structures prepared mainly using thermal oxidation of silicon. Used here are literature data as well as results obtained by authors when studying the temperature and electric field dependencies of the capacitive photovoltage. It has been ascertained that the BES system consists of a continuous U-like distribution in the silicon forbidden gap and from the discrete BES as well. There developed are two discrete BES in the thermally oxidized Si(111)-SiO₂ structure, while in the Si(100)-SiO₂ structure – four ones. These results well coordinated with ESR investigations were obtained using the method of temperature dependencies for capacitive photovoltage without application of an external electric field. As shown, application of various electric-field methods enables to determine only effective parameters of discrete and especially continuously distributed BES, which depend on the temperature of measurements, silicon resistivity and conditions of preparation of the Si-SiO₂ boundary. Considered are the features of pre-oxidation treatment of the silicon surface and its oxidation, the character of the intermediate layer between Si and SiO₂, and the influence of such external factors as annealing in various ambient atmospheres, irradiation and high electric fields as well.